Health comorbidities in children with down syndrome (DS) at Dr. Sardjito General Hospital, Yogyakarta - Suryono Yudha Patria; Agung Triono (Published by Universitas Gadjah Mada, 2024)
Down syndrome (DS) is a disease caused by trisomy of chromosome 21. The phenotype in DS leads to manifestations in several organ systems. This study aimed to identify the pattern of comorbidities in DS patients. It was a single-center, cross-sectional study at Dr. Sardjito General Hospital, Yogyakarta. Medical records of pediatric patients with DS from a period of January 2022 to May 2023 were included. Descriptive analysis was performed to demonstrate demographic and clinical characteristics. A total of 355 pediatric patients with DS were found at Dr. Sardjito General Hospital and the majority were male (196 children or 55.2%). As much as 339 children (95.49%) had comorbidities. The highest comorbidity was congenital heart disease (230 patients or 67.84%) in specifics were atrial septal defect (41 patients or 12.39%), atrioventricular septal defect (29 patients or 8.17%), and patent ductus arteriosus (28 patients or 7.88%). The second highest comorbidity was endocrine system disorders (102 patients or 30.09%), with 100 patients (28.16%) children suffering hypothyroidism. The number of children who had one comorbidity was 248 patients (69.86%), 74 patients (20.48%) had two comorbidities, and 17 patients (4.79%) had three or more comorbidities. The highest co-prevalence of the two comorbidities was congenital heart disease and endocrine system disorders (36 patients or 10.14%). The highest co-prevalence of 3 or more comorbidities was a combination of congenital heart disease, visual impairment, and hearing impairment (6 patients or 1.69%). In conclusion, 95.49% of children with DS have comorbidities. The most common comorbidity was heart defects. About 25.63% of patients had more than one comorbidity. Children with DS who have comorbidities require more attention to prevent complications and to reduce morbidity.